2022
DOI: 10.1111/ced.15337
|View full text |Cite
|
Sign up to set email alerts
|

A multicentric study on dermoscopic patterns and clinical–dermoscopic–histological correlates of basal cell carcinoma in Indian skin

Abstract: Background Literature on the dermoscopic patterns of basal cell carcinoma (BCC) in India is limited. Aim To describe the dermoscopic pattern and dermoscopic–histopathological correlation in a large cohort of patients with BCC from India, with a particular focus on skin of colour (SOC). Methods This retrospective study was conducted under the aegis of the Dermatoscopy Society of India. Clinical details were collected, and two lead authors independently analysed dermoscopic images of BCC for a predefined set of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Other frequent dermoscopic features were milky red structureless areas, arborizing vessels, short fine telangiectasias and ulceration. A previous study reported similar findings with an even higher frequency of blue pigmentation, but it was conducted in a population with darker skin color [ 20 ]. Indeed, BCCs developing in individuals with dark phototypes (IV–VI, according to the Fitzpatrick classification) display pigment more frequently, regardless of the histological subtype, as compared with BCCs in patients with fair skin [ 20 ].…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…Other frequent dermoscopic features were milky red structureless areas, arborizing vessels, short fine telangiectasias and ulceration. A previous study reported similar findings with an even higher frequency of blue pigmentation, but it was conducted in a population with darker skin color [ 20 ]. Indeed, BCCs developing in individuals with dark phototypes (IV–VI, according to the Fitzpatrick classification) display pigment more frequently, regardless of the histological subtype, as compared with BCCs in patients with fair skin [ 20 ].…”
Section: Discussionsupporting
confidence: 57%
“…A previous study reported similar findings with an even higher frequency of blue pigmentation, but it was conducted in a population with darker skin color [ 20 ]. Indeed, BCCs developing in individuals with dark phototypes (IV–VI, according to the Fitzpatrick classification) display pigment more frequently, regardless of the histological subtype, as compared with BCCs in patients with fair skin [ 20 ]. In a study by Vinay et al on 19 micronodular BCCs in Indian patients, the prevailing structure was blue pigmentation, especially blue-white veil, being as high as in 84.2% of cases, followed by nests and dots (78.9% versus 68.4%) [ 20 ].…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations